P211 Using the clinical practice research datalink (CPRD) to recruit participants from primary care to investigate chronic obstructive pulmonary disease (COPD) exacerbations. (15th November 2016) - Moore, E; Hashmi, M; Sultana, K; Chatzidiakou, L; Jones, RL; Beevers, S; Kelly, FJ; Smeeth, L; Barratt, B; Wright, M; Quint, JK
Abstract : Introduction: Traditionally, recruitment for health research involves clinicians identifying and then contacting potentially suitable participants. This can be both time-consuming and labour intensive for clinicians and researchers. Databases of Electronic Healthcare Records (EHRs) can be used as a resource through which potential study participants can be approached but is often underutilised in spite of previously being shown to be effective (Horspool et al, 2013). For a study investigating the association between air pollution and COPD exacerbations using portable air monitors and symptom diaries, we employed a relatively novel method of recruitment involving approaching patients to participate via the Clinical Practice Research Datalink (CPRD), an anonymised general practitioner (GP) records database containing ongoing primary care medical data. Methods: Patients registered at general practices within Greater London whose GP practices were part of the CPRD network were identified anonymously by CPRD using a validated codelist and algorithm developed by our team (Quint et al, 2014). GPs were able to verify the suitability of the potential participants identified and post information about the study to them. Patients could register their interest in the study directly with the research team to be enrolled in the study. Results: Feasibility screening by CPRD between January and July 2016 indicated 675 potential study participants at 20 practices and from the CPRD-supplied practice screening lists GPs identified and deemed eligible 462 patients. 462 patients were contacted and the response rate was 136/462 of which 43 (32%) were enrolled and 93 (68%) declined. The main reason for declining was related to the demands that the project entailed of looking after the air monitor and diary for 6 months. Conclusion: Patients with COPD from GP practices within Greater London were successfully screened and recruited through CPRD to participate in research over a 6 month period thus providing access to a milder cohort of research naive patients who better represent the majority of the COPD population and this method minimised input needed by the GP. This is a novel method of using EHRs to recruit participants for research that is currently underutilised.